GESTÃO COMPARTILHADA (APMs) NO PARANÁ: A HISTÓRIA DA DESCENTRALIZAÇÃO DA EDUCAÇÃO DO GOVERNO JAIME LERNER (1995-2002) - Dall’igna, Marta Beatriz dos Santos (2007)
Since the decade of 1990 an education speech led by the World Bank (MB) it was impinged Latin America fomenting order words as citizenship, justness, partnership and Shared Administration (GC), with significant alterations in the paper of the National State and being authenticated inside of the public schools. This work is devoted the clarification of the transition of the passage of the school citizen's ideal for the ideal of excellence school, changes that they signaled the passage of the Democratic Administration (1991-1994) in the government's of the State of Paraná administration, Roberto Requião and of the Shared Administration (1995-2002), in Jaime Lerner Government in order to elucidate a doubt on that model implemented in Paraná as for their true objectives: mobilization of the Association of Parents and Masters (APMs) for participation of the parents or decentralization of responsibilities? Does the research investigate as he/she felt the process of reconfiguration of the public education system in the State of Paraná with the application of trainings of GC for AMPs accomplished in the University of the Teacher (UP) in the period from 1995 to 2002? Objectively, he understands the process of reconfiguration of the public education system in Brazil, in specific in the State of Paraná in the delimited period, that they approach the Programs of Institutional Development for the Project of Total Quality (PQE) financed by BM in trainings accomplished in UP for APMs in Faxinal do Céu starting from the Proposal of GC, he interprets what demands of the capitalism assist the education for the State, it accompanies how redefined were being the concepts disseminated in the field of the education in the trainings accomplished with APMs in UP, and, it analyzes as the guidelines of the education programs of the General office of State of the Education of Paraná were implemented (SEED) and the nature of the administrative and pedagogic mechanisms, servants or altered in the sense of rendering them. The research felt in bibliographical studies, analysis of the documents of SEED, observation (in loco) of the works developed by the Consultant ship of Education Mobilization (he AME), analysis of the appraisers' of the Seminars of GC reports accomplished during the period delimited by the research and the comparison of those actions of the State to the Pedagogic Political Project (PPP) of two schools: the State School La Salle and the São João Bosco school, located in the municipal district of Pato Branco. The questionnaires with open and closed subjects were driven 98 people, presidents of APMs, teachers, parents, volunteers and to the managers of the two schools. Interview was accomplished with the organizers of the seminars of GC, the team of the he AME and the coordinator of the magazine Administration in Net, including recordings, filming and pictures in the places, UP and SEED. The results confirmed a model of administration of the education that excelled for the decentralization of responsibilities of the State and for the summons of the civil society for what was called GC. It was ended that the process of reconfiguration of the public education system in the State of Paraná in the period from 1995 to 2002 can be recognized by the results obtained in the researches confirming that GC in the Education of Paraná went a government artifice to decentralize the responsibilities of the State, understood and here registered, that historical period.